Strategi Pemasaran pada Produk SAHARA (Simpanan Hari Raya Idul Fitri) di KSPPS Nur Indah Abadi Kencong - Roychan Maulana Arbyansyah; Dovi Iwan Musthofa Habibillah (Intitut Agama Islam Nasional Laa Roiba Bogor, 2024)
This study aims to analyse the marketing strategy of SAHARA products offered by Nur Indah Abadi Kencong Sharia Financial Services Cooperative (KJKS). Using a qualitative approach with a literature study, this research analyses the profile of SAHARA products, SWOT analysis, and marketing strategies that have been implemented. The results show that SAHARA products have great potential, but there are still some weaknesses that need to be improved. The SWOT analysis identified the strengths, weaknesses, opportunities, and threats facing SAHARA products. In addition, this study also identifies several marketing strategies that have been implemented by KJKS, and provides recommendations for improving marketing strategies in the future. This study concludes that to improve the success of SAHARA products, KSPPS needs to focus on strengthening branding, utilising digital marketing, and strategic partnerships.